Health and safety at hazardous waste sites the investigator's and remediator's guide to HAZWOPER - Maslansky, Steven P. (Van Nostrand Reinhold, 1997)
Provides all the basic background information necessary to investigate and clean up hazardous waste sites safely and efficiently. Serves as a main text for any safety and hazardous materials operations courses in the U.S., Canada, and overseas.